2020
DOI: 10.1098/rsos.191020
|View full text |Cite
|
Sign up to set email alerts
|

Sexual frequency is associated with age of natural menopause: results from the Study of Women's Health Across the Nation

Abstract: It is often observed that married women have a later age of natural menopause (ANM) than unmarried women; however, the reason for this association is unknown. We test an original hypothesis that sexual frequency acts as a bio-behavioural mediator between marital status and ANM. We hypothesize that there is a trade-off between continued ovulation and menopause based on the woman's chances of becoming pregnant. If a woman is sexually inactive, then pregnancy is impossible, and continued investment in ovulation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
2
6
0
Order By: Relevance
“…This difference might be attributed to the variations in genetic and environmental factors [ 28 ]. In this study we found no association between marital status and any of the menopause categories, which was in line with the findings of some previous studies [ 19 , 29 , 30 ]. Studies that found a significant role for marital status in age at menopause related this effect to a better socioeconomical status, better family support, higher hygiene level, and better quality of life in married women compared to single women [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…This difference might be attributed to the variations in genetic and environmental factors [ 28 ]. In this study we found no association between marital status and any of the menopause categories, which was in line with the findings of some previous studies [ 19 , 29 , 30 ]. Studies that found a significant role for marital status in age at menopause related this effect to a better socioeconomical status, better family support, higher hygiene level, and better quality of life in married women compared to single women [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Married women have been reported to reach menopause at a later age [12]; however, there is much discussion around how these two factors may be linked and whether the association may be confounded by the frequency of sexual activity, parity and socio‐economic status [13]. Evidence to suggest an association between menopausal status and employment status is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…An example of a short-term benefit is the increased pain threshold for a short period after female genital stimulation (Whipple & Komisaruk, 1985). An example of an intermediate-term benefit is the postponement of natural menopause (and the accompanying hypoestrogenism) in women with more frequent sex (Arnot & Mace, 2020). Examples of long-term benefits are the decreased risk for prostate cancer in men who over the decades have ejaculated more frequently (Rider et al, 2016), increased longevity in men who continued with sexuality, and increased longevity in women who have had a more satisfying sexual life (Palmore, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…Post-menopausal women who continue to be sexually active, show less vaginal atrophy and higher levels of androgens and gonadotropins (Leiblum et al, 1983). Women who are more sexually active also show slower transitions to menopause and the accompanying hypoestrogenism (Arnot & Mace, 2020).…”
Section: Sexual Function Self-maintenancementioning
confidence: 99%